The effects of first language literacy skills on second language literacy skills for native Spanish and native English speakers - Watkins-Mace, Sarah P. (Kansas State University, 2006)
It has long been believed that how well one reads and writes in his/her first language will help a learner when trying to read and write in a second language. In an attempt to explore this issue more thoroughly, the researcher administered the Spanish Idea Proficiency Test (IPT) and the English Idea Proficiency Test form 3B, along with a questionnaire obtaining specific demographic data (first semester second language grade, grade point average, gender, grade in school, number of semesters studied the second/foreign language, and the number of languages the student had studied) to 96 Kansas high school students (48 Native Spanish speakers learning English in an English as a second language environment; 48 Native English speakers learning Spanish in a foreign language setting). First, the researcher wanted to determine if first language literacy skills, along with demographic data, predicted second language proficiency scores. Using the 5 reading subscales and the 3 writing subscales from the IPT, as well as the 6 variables from the demographic data, a multiple linear regression was run, along with regressions for each subgroup. It was determined that the 14 variables accounted for 83% of the variance. Second, the researcher wanted to determine the nature of the relationship between first language literacy skills and second language literacy skills. To this end, several Pearson’s r were figured. While a negative relationship for the first and second language proficiency scores was found, a slight positive relationship was found between the first and second language scores for the two subgroups. Additionally, a significantly positive relationship was found for first and second language reading and writing proficiency scores for the native Spanish speakers. Also, a significant positive relationship was found for first semester second language grade and second language reading scores for native English speakers. Third, the researcher wanted to determine if there was a difference between the two subgroups’ second language proficiency scores when controlling for the length of time studied. When an ANCOVA was conducted, there was found to a significant difference between the proficiency scores of the two subgroups, with the native Spanish speakers having a higher mean.
Keywords: English as a Second Language; Developmental Interdependence Hypothesis; Foreign language learners; Second language learners; Bilingual education; Biliteracy; Education, Bilingual and Multicultural (0282); Education, Language and Literature (0279); Education, Reading (0535)